Localizing and analyzing defects in AlGaN/GaN HEMT using photon emission spectral signatures. (November 2017) - Moultif, Niemat; Divay, Alexis; Joubert, Eric; Latry, Olivier
Abstract: This paper presents a reliability study of an AlGaN/GaN high electron mobility transistor (HEMT) by the photon emission (PE) and the spectral photon emission (SPE) techniques. The backside PE analysis of the studied AlGaN/GaN HEMT identifies PE signatures at the gate foot edge on the drain side, and at two new positions: under the middle of the gate or at the gate foot edge on the source side. The SPE analysis of the localized signatures defines the deep level trap energy Ec—1.35 eV which seems to be related to an interstitial carbon defect that forms along dislocations, or an omnipresent defect such as C or possibly dislocations. Highlights: Photoemission and Spectral Photoemission is used to identify some defect in AlGaN/GaN HEMT transistors. Backside preparation and probing the component shows photoemission signature of leakage current conduction. For the first time in backside, two new positions are localised at the middle and at the foot edge on the source side. The energy level at 1.35eV should be attributed to interstitial carbon defect along dislocations or Carbon or dislocations. Application is used on AlGaN/GaN 25W power bar of 0.5μm gates HEMT.